2016
DOI: 10.1186/s12862-016-0663-7
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical genetic structure shaped by topography in a narrow-endemic montane grasshopper

Abstract: BackgroundUnderstanding the underlying processes shaping spatial patterns of genetic structure in free-ranging organisms is a central topic in evolutionary biology. Here, we aim to disentangle the relative importance of neutral (i.e. genetic drift) and local adaptation (i.e. ecological divergence) processes in the evolution of spatial genetic structure of the Morales grasshopper (Chorthippus saulcyi moralesi), a narrow-endemic taxon restricted to the Central Pyrenees. More specifically, we analysed range-wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 97 publications
(111 reference statements)
7
74
0
Order By: Relevance
“…Accordingly, landscape genetic analyses indicated that genetic differentiation was explained by both the geographical distance among populations and resistance distances defined by topographic roughness (Table ). These results might reflect the low dispersal capability of the studied taxon, males being brachypterous and females micropterous, and are comparable to those obtained by previous studies showing the impact of steep slopes and complex landscapes on structuring genetic variation in montane/alpine grasshoppers (Noguerales, Cordero, et al, ). Genetic structure analyses showed that the split of the different populations at local/regional scales followed a longitudinal cline rather than a segregation of alpine and Mediterranean‐montane populations (e.g., SET and BAT), indicating no support for either ecologically driven divergence or the taxonomic separation between the supposedly Mediterranean O. navasi and the alpine O. antigai .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Accordingly, landscape genetic analyses indicated that genetic differentiation was explained by both the geographical distance among populations and resistance distances defined by topographic roughness (Table ). These results might reflect the low dispersal capability of the studied taxon, males being brachypterous and females micropterous, and are comparable to those obtained by previous studies showing the impact of steep slopes and complex landscapes on structuring genetic variation in montane/alpine grasshoppers (Noguerales, Cordero, et al, ). Genetic structure analyses showed that the split of the different populations at local/regional scales followed a longitudinal cline rather than a segregation of alpine and Mediterranean‐montane populations (e.g., SET and BAT), indicating no support for either ecologically driven divergence or the taxonomic separation between the supposedly Mediterranean O. navasi and the alpine O. antigai .…”
Section: Discussionsupporting
confidence: 90%
“…Collectively, our analyses rejected the current hypothesis of two species and indicated that populations assigned to O. antigai and O. navasi show a distribution of genetic variation that (a) does not match with their respective taxonomic designation and (b) is incompatible with ecological/environmental speciation. Our results show the presence of two main genetic groups corresponding to an east–west split analogous to that found in many other Pyrenean taxa (Wallis, Waters, Upton, & Craw, ) and a marked genetic differentiation at local spatial scales reflecting limited population connectivity across the abrupt landscapes characterizing the study region (e.g., Noguerales, Cordero, & Ortego, ).…”
Section: Discussionsupporting
confidence: 78%
“…We used a backward procedure to select final models, eliminating nonsignificant variables from an initial full model including all explanatory predictors. We tested the significance of the remaining variables again until no additional term reached significance (Noguerales et al., ; Ortego, Gugger,et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we assess the potential role of geography, environment (specifically climate) and female preference in modelling spatial patterns of genetic and phenotypic (morphological and acoustic) divergence in Chorthippus cazurroi (Bolívar, 1898), an annual alpine grasshopper endemic to the Cantabrian Mountains, north‐western Spain. Previous studies have shown that isolation and habitat determined genetic and phenotypic differentiation in grasshoppers (Hernández‐Teixidor et al., ; Noguerales, Cordero, & Ortego, ; Ortego, Aguirre, & Cordero, ; Sathyan, Engelbrecht, & Couldridge, ). Orthopterans represent also an ideal model to address sexual selection issues (Greenfield, ; Robinson & Hall, ), since female uses male song and morphology both for species recognition and selection between conspecific males (Klappert & Reinhold, ; Saldamando et al., ).…”
Section: Introductionmentioning
confidence: 98%